Hubungan Penerapan Deep Learning dengan Kemampuan Berpikir Kritis Siswa pada Pembelajaran Informatika di SMPN 9 Pariaman - Selvina Aulia; Zulfani Sesmiarni (MASALIQ, 2026)
The suboptimal critical thinking skills of students in Informatics learning indicate the need to implement a learning approach that promotes active cognitive engagement, one of which is deep learning based on the principles of mindful, meaningful, and joyful learning. This study aimed to analyze the relationship between the implementation of deep learning and students’ critical thinking skills in Informatics learning at SMPN 9 Pariaman. The study employed a quantitative approach with a descriptive correlational design. The study population comprised all eighth-grade students at SMPN 9 Pariaman, with a sample of 53 students. Data were collected using a questionnaire and analyzed through descriptive analysis, normality testing, linearity testing, and the Pearson product-moment correlation test. The results showed that the implementation of deep learning obtained a mean score of 94.75, whereas critical thinking skills obtained a mean score of 100.47. The correlation test yielded a correlation coefficient of 0.848 with a significance value of p < 0.001, indicating a positive, significant, and very strong relationship between the implementation of deep learning and students’ critical thinking skills. These findings confirm that the better the implementation of mindful, meaningful, and joyful principles in Informatics learning, the higher the students’ critical thinking skills. Therefore, deep learning can serve as a foundation for teachers and schools in designing more effective Informatics learning to develop students’ critical thinking skills.